Investigation of the performance of ceramic tools of alumina doped with magnesium oxide in the dry machining of compacted graphite iron - Sousa, T. A. [UNESP]; De Paula, M A [UNESP]; Konatu, R. T. [UNESP]; Ribeiro, M. V. [UNESP]; De Campos, E [UNESP]; Souza, J. V.C. [UNESP] (IOP Publishing, 2019)
In the search for materials to serve the automotive industry, mainly in the application in engine blocks, the most interesting material is the vermicular cast irons, which must have superior physical and mechanical properties. However, one of the disadvantages for the industry is the difficulty of machining this class of materials, due to its microstructure. It is important for the process of machining to understanding the relation between the cutting tools and the process parameters. as their rapid wear and crash of the cutting tool causes many machine stops, which is directly impact the high production costs. The research for viable alternatives to improve the machinability of compacted graphite iron (CGI), the ceramic inserts are in highlighted. The objective of this study was to dry turning the vermicular cast iron of class 450 with a ceramic cutting tools of alumina doped with magnesium oxide, developed on an experimental scale for machining. For the machining test, the following conditions was used: Cutting speeds (Vc) of 200 and 500mmin-1; feed rate (f) of 0.1 and 0.3mm/rot-1 and depth of cut (doc) of 0.5 and 1.0 mm. For the process of machining was used a CNCmachining center and compare the variables: Flank wear (cutting tool), roughness Ra and Rt (workpiece). The wear of the cutting tools was analyzed using a scanning electron microscope (SEM) equipped with (EDS). This work obtained the best results using the condition: Vc of 200mmin-1, f 0.1 mm, doc 1.0mmshowed the lower value of flank wear and roughness. The main wear mechanism observed was abrasion for all the conditions analyzed.
Keywords: Ceramic cutting tool; Dryturning; Machining of cgi; Wear mechanism